2017
DOI: 10.1159/000481343
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor for Vital Signs Fluctuation during Colonoscopy under Conscious Sedation Consisting of Midazolam and Meperidine

Abstract: Background: Sedatives or analgesics are widely used to relieve a patient’s discomfort during colonoscopy (CS). Although cardiopulmonary adverse events are sometimes experienced during the examination, the risk factors for vital signs fluctuation (VSF) have not been fully elucidated. This study thus aimed to identify the risk factors for VSF during the examination, as well as to evaluate the frequency and the degree of VSF. Summary: A total of 755 consecutive subjects who received CS under endoscopist-administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The primary outcome was all cardiopulmonary adverse events including tachycardia, bradycardia, hypertension, transient hypotension, respiratory depression, oxygen desaturation, and fatal arrhythmia. The secondary outcomes were the following: vital signs fluctuation (VSF), which was defined as transient hypotension (SBP < 90 mm Hg or at least 20 mm Hg less than the baseline value, even at least once during the procedure) and oxygen desaturation (SpO2 < 90% on room air or < 95% on 2L/min oxygen) [ 22 ] ; adverse events disturbing the procedure such as belching, severe coughing, needs for restraint, and myoclonus; and sedation-related outcomes including induction time, total procedure time, awake time, patients’ and endoscopist's satisfaction scores, and frequency of recall.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was all cardiopulmonary adverse events including tachycardia, bradycardia, hypertension, transient hypotension, respiratory depression, oxygen desaturation, and fatal arrhythmia. The secondary outcomes were the following: vital signs fluctuation (VSF), which was defined as transient hypotension (SBP < 90 mm Hg or at least 20 mm Hg less than the baseline value, even at least once during the procedure) and oxygen desaturation (SpO2 < 90% on room air or < 95% on 2L/min oxygen) [ 22 ] ; adverse events disturbing the procedure such as belching, severe coughing, needs for restraint, and myoclonus; and sedation-related outcomes including induction time, total procedure time, awake time, patients’ and endoscopist's satisfaction scores, and frequency of recall.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced age significantly increases perioperative morbidity and mortality in elderly patients 20 and has been confirmed to be an independent risk factor for anesthesia-related adverse events 21 , 22 . Studies have shown that compared with propofol, remimazolam is more effective in sedation and impacts less on the respiratory and circulatory systems 23 , and its advantages may be more prominent when used for anesthesia and sedation in the elderly 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge gap might be affecting PSA practice in Japan. Analgesics with a long time to peak effect, such as meperidine, are still widely used for PSA in Japan . Although there is ongoing debate over what the ideal medications for PSA are, experts generally agree that ideal pharmacological characteristics of medications for PSA should include rapid onset of action and short time to peak effect .…”
Section: Discussionmentioning
confidence: 99%